2020
DOI: 10.1002/aenm.202002019
|View full text |Cite
|
Sign up to set email alerts
|

Phase Engineering of Nanomaterials for Clean Energy and Catalytic Applications

Abstract: Phase engineering of nanomaterials (PEN) is critically important for the preparation of nanomaterials with new phases, which are key for the investigation of phase‐dependent physicochemical properties and applications. This essay presents the state‐of‐the‐art development of PEN for the unique properties of nanomaterials with unconventional phases and their applications in energy storage and conversion and catalytic reactions. Finally, personal perspectives on the challenges and future opportunities of PEN in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 107 publications
0
93
0
Order By: Relevance
“…The unique crystal phases endow them with appealing properties and promising applications in catalysis. [3,8,9,[27][28][29][30][31][32][33] The ability to synthesize noble-metal-based nanostructures with different crystal phases allows the exploration of phase-dependent properties and applications, [34][35][36] suggesting that the crystal phase of noble-metal-based nanomaterials is also critical in determining their physiochemical properties in addition to their composition, size, and morphology. For example, a recent study showed that the L1 2 Pt 3 Mn nanoparticles exhibit superior electrocatalytic activity toward the ORR as compared to their counterpart with the conventional facecentered cubic (fcc) phase.…”
Section: Introductionmentioning
confidence: 99%
“…The unique crystal phases endow them with appealing properties and promising applications in catalysis. [3,8,9,[27][28][29][30][31][32][33] The ability to synthesize noble-metal-based nanostructures with different crystal phases allows the exploration of phase-dependent properties and applications, [34][35][36] suggesting that the crystal phase of noble-metal-based nanomaterials is also critical in determining their physiochemical properties in addition to their composition, size, and morphology. For example, a recent study showed that the L1 2 Pt 3 Mn nanoparticles exhibit superior electrocatalytic activity toward the ORR as compared to their counterpart with the conventional facecentered cubic (fcc) phase.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from graphene, ultrathin 2D transition metal dichalcogenide (TMD) nanosheets are receiving increasing attention due to their unique chemical and electronic properties, endowing them with great potential in various applications such as sensors, catalysis, biomedicine, (opto)electronics, and energy storage devices. [ 22–38 ] With similar 2D configuration with GO and rGO, TMD nanosheets also could serve as a new class of promising building blocks to be assembled into various nanostructures. [ 6,39 ] Previously, we developed a general polymer‐assisted assembly strategy for the self‐assembly of single‐ or few‐layer TMDs, including MoS 2 , TiS 2 , TaS 2 , TaSe 2 and WSe 2 , and GO, into helical nanofibers and nanorings with the aid of vortex.…”
Section: Introductionmentioning
confidence: 99%
“…The second strategy is through manipulating the crystal phase of a compound. [14][15][16] While a change in crystal phase may have a smaller effect on reactivity tuning, e.g. <0.5 eV, than that of local coordination environment, it still has a significant impact on the catalytic activity due to structure sensitivity, as demonstrated by Liu et al regarding hexagonal close-packed (hcp) Co versus face centered-cubic (fcc) Co for Fischer-Tropsch (FT) synthesis, [17][18][19] and Wang et al regarding cubic In 2 O 3 versus hexagonal In 2 O 3 for the reverse water gas shift (RWGS) reaction.…”
Section: Introductionmentioning
confidence: 99%